FOCUS GROUP DISCUSSIONS: EXPLORATION OF PSYCHOLOGICAL AND NEUROLOGICAL FUNCTIONING OF ELDERLY IN GILGIT & LAHORE, PAKISTAN - Najam, Najma; Kanwal, Rabia Hussain; Kausar, Rukhsana; Fatima, Hira (European Scientific Journal, ESJ, 2014)
In Pakistan, elderly population has been neglected by the researchers and policy makers alike and it has resulted in compromised quality of life of the ageing population. The present study examined the psychological and neurological functioning of the elderly in Gilgit & Lahore, Pakistan in order to explore and identify the illicit psychological, emotional, and cognitive problems and challenges encountered by the elderly using snow-ball and purposive sampling technique. These regions were selected for comparison as Lahore is highly urbanized, large city and Gilgit a small mountain bound valley. Ten focus group discussions had been conducted in two groups in Gilgit: 5 younger groups and 5 elderly groups (sample of 50; 25 elderly & 25 younger; 05 participants in each group). Whereas at Lahore side, 2 focus group discussions were conducted in Lahore: 1 younger group (8; 2 younger men & 6 younger women) and 1 elderly group (7 elderly); 4 indepth interviews were also conducted from 2 younger & 2 elderly in Lahore. Preliminary findings are reported. Findings suggest that the elderly play a very significant role in both Gilgit and Lahore societies and culture. Elderly were actively engaged in daily life activities such as community activities, domestic work, farming, breeding of domestic animals but with the passage of time their level of self-efficacy had decreased and negatively influencing short-term memory, intelligence, attention span, concentration as well as physical weaknesses in doing tasks. Lack of formal education of the elderly is also reported to be possibly a hindrance in understanding the context of youth. Younger responded that they do not feel comfortable to share matters with them as they have hierarchal relationship with their elders. Diverse responses were reported by younger group but they agreed to the point that elders were influential and decision makers of the society and honored as backbone of the society for transmission of culture and traditions. Elders expect from their young family members must realize their contribution to develop the sense of responsibility for their home, community, region and country as people of Gilgit have a high dependency on the natural environment, without access to many modern facilities due to remoteness and limited accessibility of this region. However, elders of Lahore expect from their family to spent time with them and take out some spare time for them from their busy materialistic life activities. This is the first attempt to understand the issues, the findings are expected to have implications for improving quality of life of the elderly, designing interventions, support system and rehabilitation services to help them. This project was funded by the Research Grant from Higher Education Commission to the first author, acknowledgement of all those involved in the data collection.